Security Principles of Smart Grid Networks - Holík, Filip; Horálek, Josef (My University, 2018)
Increased power consumption and power supply variability require implementation of modern tools for intelligent management and control of grid networks. One of the most promising advancements in technology is the Smart Grid network. Unfortunately, this technology is still rapidly evolving and at this point contains many security issues. As recent attacks have shown, only some of these issues are known. This paper is using a systematic approach to detect these issues and to analyse all types of attacks on the Smart Grid networks. The last part of the paper proposes solution models for securing Smart Grid networks against found vulnerabilities.
Bezpečnostní principy Smart Grid sítí
Keywords: Smart Grid security; Smart Grid attacks; Risk management; Security risks; Bezpečnost Smart Grid sítí, útoky na Smart Grid sítě, risk management, bezpečnostní rizika